Injury Prevention Activities in US Schools, School Health Policies and Practices Survey 2014. (11th April 2022) - Miller, Gabrielle F.; Wilson, Lauren; Rice, Ketra; DePadilla, Lara; Mercado‐Crespo, Melissa; Jones, Sherry E.
ABSTRACT: BACKGROUND: Exposure to injury and violence early in life increases the risk of experiencing injury and violence later in life. In 2019, the top 3 leading causes of death among 15‐ to 18‐year‐olds in the United States were unintentional injury, suicide, and homicide. This study examines the extent to which schools promote injury and violence prevention. METHODS: This study examined injury‐ and violence‐related school policies and practices using nationally representative data from the 2014 School Health Policies and Practices Study. The social ecological model served as the theoretical framework to identify level of impact. RESULTS: For many injury‐related topics, more than 75% of schools nationwide had relevant policies and practices to address those topics. However, this study showed differences in schools' injury‐related policies and practices by urbanicity. CONCLUSIONS: Understanding and identifying gaps in school policies and practices is essential for reducing and preventing the injury and violence children experience. Collecting data on school policies and practices allows for better monitoring and evaluation to determine which are efficacious and aligned with the best available evidence.